2000
DOI: 10.1017/s0950268899003969
|View full text |Cite
|
Sign up to set email alerts
|

Serological prevalence to six leptospiral serovars in cattle in Asturias (Northern Spain)

Abstract: SUMMARYThe prevalence of antibody to six serovars of Leptospira interrogans in cattle in Asturias (Northern Spain) was determined by the microscopic agglutination test (MAT). Using 50 % agglutination or lysis at a dilution of 1 : 10 or more as the criteria for seropositivity, 371 of 3578 (10n36 %) animals were found to react with one serovar. The most commonly detected serovars were pomona (5n59 %) and grippotyphosa (2n37 %), whilst serovar hardjo (0n75 %), icterohaemorrhagiae (0n64 %), poi (0n64 %) and autumn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…All sera were tested by MAT, which is the most widely used reference diagnostic test because of its high sensitivity and specificity and its ability to identify to serogroup or serovar level [3,18,19,21]. 1: 10 in a serosurvey of cattle in Asturias northern Spain [10], 1 :24 in a serosurvey of meat inspectors in New Zealand [23], 1: 30 in a serosurvey of leptospiral infections in dairy cows in Galicia, Spain [24], 1 :40 in a serosurvey of domestic animals in West Malaysia [4], and 1:50 in a serosurvey of beef cattle in central Queensland [8] and in a serosurvey of buffalo herds in Italy [25]. 0 % and 73 .…”
Section: Discussionmentioning
confidence: 99%
“…All sera were tested by MAT, which is the most widely used reference diagnostic test because of its high sensitivity and specificity and its ability to identify to serogroup or serovar level [3,18,19,21]. 1: 10 in a serosurvey of cattle in Asturias northern Spain [10], 1 :24 in a serosurvey of meat inspectors in New Zealand [23], 1: 30 in a serosurvey of leptospiral infections in dairy cows in Galicia, Spain [24], 1 :40 in a serosurvey of domestic animals in West Malaysia [4], and 1:50 in a serosurvey of beef cattle in central Queensland [8] and in a serosurvey of buffalo herds in Italy [25]. 0 % and 73 .…”
Section: Discussionmentioning
confidence: 99%
“…According to one finding, large communally grazed herd size enhances the exposure potential, through increased contact at common feeding and watering points, often contaminated with urine from infected domestic or wild rodent carriers (Quinn et al 2000). In such circumstances, cattle or goats/sheep of unknown diseases status might mix and often grazed Table 3 The distribution of positive sera by L. interrogans serovar antibodies levels a Equal to or greater than 1:160 positive reactors together and resulted in spreading infected urine and transmission of disease among herds (Espi et al 2000;Victoriano et al 2009). Also, the presence of a breeding bull on herd showed an unexpected outcome in the univariable regression, being associated with a higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous serological studies of Leptospira spp. in domestic animals in Asturias (Northern Spain) showed that Bratislava was the most prevalent serovar (Espí et al, 2000(Espí et al, , 2001.…”
Section: Leptospira Spp Red Deer (Cervus Elaphus) Fallow Deer (Dama Dmentioning
confidence: 99%